(untitled) (CIPEEX, 2025)
Introduction: The role of the biomedical practitioner in the Blood Bank was formally recognized by Biomedicine in 2002 by resolution n. 78. This area works in the blood transfusion process, from the verification of blood compatibility to the separation and production of blood components and blood products. (1) Objective: To conduct a bibliographic study on the role of biomedical professionals in blood banks, highlighting their responsibilities and importance in the blood transfusion process. Methodology: Bibliographic research of a narrative nature was carried out between January and March 2025. The following keywords were used: Biomedical scientist (AND) blood bank (OR) transfusion medicine. The searches were conducted in the PubMed and SociELO databases, and included complete articles published in Portuguese and English, which addressed the role of biomedical professionals in blood banks, especially in the screening process, production of blood components and practices related to blood transfusion, studies that were not directly related to biomedical practice in this area were excluded. Results: The research showed that the role of biomedical in blood banks has become increasingly relevant in the face of the growing demands for transfusion safety and efficient management of blood components. (2,3) Conclusion: The role of biomedical professionals in blood banks has been established as strategic, combining technical skills and innovation to ensure the safety and efficacy of hemotherapy.